2001
DOI: 10.1164/ajrccm.164.1.2008022
|View full text |Cite
|
Sign up to set email alerts
|

Clara Cell Secretory Protein Oxidation and Expression in Premature Infants Who Develop Bronchopulmonary Dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) is a chronic lung disease that affects prematurely born infants and appears to evolve in part from early inflammatory responses in the lung. The inflammatory responses have been associated with protein and lipid oxidation in tracheal aspirate fluids. The present study was designed to test the hypothesis that in the first week of life specific oxidations and/ or altered expressions of proteins would be observed in tracheal aspirate fluids in infants who would subsequently develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 34 publications
7
64
1
Order By: Relevance
“…Average elimination half-lives were 11.6 h in the 1.5-mg/kg group and 9.9 h in the 5.0-mg/kg group, consistent with results from animal models (18).…”
Section: Patientssupporting
confidence: 86%
See 1 more Smart Citation
“…Average elimination half-lives were 11.6 h in the 1.5-mg/kg group and 9.9 h in the 5.0-mg/kg group, consistent with results from animal models (18).…”
Section: Patientssupporting
confidence: 86%
“…CC10 concentrations have been demonstrated to correlate negatively with the concentration of inspired oxygen required by preterm infants with respiratory distress syndrome (RDS) (17). Most recently, Ramsey et al (18) demonstrated that not only were CC10 concentrations lower in TAF from infants who either died or developed BPD, but also the limited amount of available CC10 was oxidized and demonstrated less immunoreactivity relative to controls.…”
mentioning
confidence: 99%
“…SCGB1A1 has immune modulatory properties Zhang et al, 2000), and a decrease of SCGB1A1 is observed in lung diseases such as COPD and bronchopulmonary dysplasia. Thus, a loss of SCGB1A1 may contribute to the pathogenesis of these disorders (Ramsay et al, 2001;Thomas et al, 2010;Tsoumakidou et al, 2010). In contrast to Cebpa DLE mice, Cebpa…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…CCSP concentrations have been demonstrated to correlate negatively with the concentration of inspired oxygen required by preterm infants with RDS [64]. In a prospective study, CCSP levels in tracheal aspirates were lower from day one after birth in infants who developed BPD compared to those who did not [65].…”
Section: Clara Cell Secretory Proteinmentioning
confidence: 97%